A second New World hoverfly, Toxomerus floralis (Fabricius) (Diptera: Syrphidae), recorded from the Old World, with description of larval pollen-feeding ecology - Jordaens, Kurt; Goergen, Georg; Kirk-Spriggs, Ashley H.; Vokaer, Audrey; Backeljau, Thierry; Meyer, Marc De (Zootaxa, 2015)
Recently (2013–2014), several hoverfly specimens from two localities in Benin and Cameroon (West and Central Africa) were caught from a species that we could not identify using existing identification keys for Afrotropical Syrphidae. Specific identification as Toxomerus floralis (Fabricius) was accomplished using morphology and various Neotropical identification keys. Corroboration of this identification was made by sequencing of the standard COI barcode region and a subsequent BLAST-IDS in BOLD that revealed a 100% sequence similarity with Toxomerus floralis from Suriname (South America). Species identification was further supported by sequencing parts of the nuclear 18S and 28S rRNA genes. The species is widespread in Togo, Benin, Nigeria and Cameroon, and eggs, larvae and adults are abundant at several localities. Yet, the full extent of its geographic distribution within tropical Africa remains to be determined. This is only the second known established introduction of a non-African hoverfly species in the Afrotropics. Interestingly, the larvae of the species have been reported as predators of Aphididae and Delphacidae but we found them to be pollenivorous, which is a rare feeding mode within the subfamily Syrphinae. Moreover, it is the only known Syrphinae species of which the larvae feed on pollen from two plant species from different families (Cyperaceae and Orobranchaceae). This example illustrates how DNA barcoding may allow a fast and accurate identification of introduced species.